Examining personal memory in film: A reflection of documenting memory-stories in Reimagining Memories - Mathafeng, Refiloe (Centre for Film and Media Studies, 2024)
My film, Reimagining Memories, explores my grandmother's childhood. Some of her most cherished memories are her trips between Lesotho and Cape Town and the time she would spend in the city. With clarity, attachment and a sense of longing, she often never misses an opportunity to reminisce about her travels. She longingly talks about her train trips from Gugulethu to Cape Town CBD, the beach and the home she shared with her brothers and sisters. These are the stories I grew up hearing, and when she was diagnosed with dementia in 2019, these memories stayed with her the most. At its core, Reimagining Memories interrogates space, remembering and the storytelling aspect of orality that has allowed my grandmother's memory-stories to exist inter-generationally. The concept of orality is integral to the film and is what inspired its making. Based on stories of her childhood that I heard growing up, my film visually reimagines what my grandmother's childhood between two worlds would have looked like had she had access to technologies that would allow her to document them. Instead, it is through telling that her memory-stories have been preserved and transmitted down generations. Based on the film, this mini-thesis examines the representation of personal memory using cinematic language and the documentary genre. It utilizes three conventions of documentary, namely testament (interviews), archive and experimentation, to reimagine my grandmother's memory stories while simultaneously interrogating what it means to remember Cape Town in the 1950s during a time of political unrest, with great fondness. In conjunction with my film, this mini-thesis highlights the selectiveness and subjectivity ingrained in the process of an individual's act of remembering. In documenting these stories, the film itself becomes a memory – performing new meanings and alternative ways of engaging with orality, questions of memory and remembering.